GAMBARAN HIGIENE SANITASI PENGOLAHAN MAKANAN DAN KEJADIAN DIARE SERTA STATUS GIZI NARAPIDANA LAKI-LAKI USIA 18-20 TAHUN DI LEMBAGA PEMASYARAKATAN KELAS II A ANAK TANJUNG GUSTA MEDAN TAHUN 2015 - retno galuh alfia; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
The safety food for consumption basically is a meal which is processing with  concern on the principles of food hygiene and sanitation. If the food hygiene and sanitation come from bad food processing, so it will produce a source of disease transmission for those who consume and if health disfunction, it will eventually cause problems on nutritional status. The objective of this research is to describe the hygiene and sanitation of food processing, incidence of diarrhea and nutritional status of male prisoners aged 18-20 years in the Correctional Institution Class II A Children's Tanjung Gusta Medan 2015. This research was descriptive with the primary data were gathered by conducted interview/observation to food processing officers and prisoners, the while secondary data were gathered from the administration and the health care section Penitentiary Class II A Children's Tanjung Gusta Medan. The population includes 7 food processors officers and 135 prisoners. Samples were 7 food processing officers and 57 food prisoners. The results showed that the hygiene and sanitation of food processing in Correctional Institution Class II A Children's Tanjung Gusta were not good which is seen from the aspect of food handler officer, food processing place and supplies and equipment in food processing. Incidence of diarrhea in male prisoners aged 18-20 years in the last 1 month was 31 people (54.39%) from 57 samples. The nutritional status of prisoners based on the Body Mass Index (BMI) was showed that most of prisoners aged 18 years which is 5 people (55,56%) were included in thin category, 4 people (44,44%) were normal category and nothing is included  in the category of obese. Based on the results of the research, it is  suggested to officer to utilized more food processing facilities and also being informed about the importance of hygiene and sanitation in food processing. It is also needs to make an improvement of food processing  and complement the existing facilities to support hygiene and sanitation in food processing in place Penitentiary Class II A Children's Tanjung Gusta Medan. Keywords    : Hygiene and Sanitation Of Food Processing, The Incidence Of Diarrhea, Nutritional Status Of Inmates, Correctional Institution.